Integral Agroforestal plot with Sapindus saponaria associated with aromatic and medicinal species to conserve the ecosystems - J Jhoncon; S Poma; N Trinidad; Y Zeballos; G Quiroz (Global Journal of Ecology - Peertechz Publications, 2023)
The propagation and processing of Sapindus saponaria, (Boliche) and Caesalpinea spinosa (Tara) will make it possible to manage ecosystems sustainably, obtaining biological soap and natural dyes and contribute to the fight against climate change, since plant cover is increased and to the capture of CO2, reducing the pressure of greenhouse gases, increasing the production of oxygen and at the same time generating industry for the production of biodegradable cleaning and beauty products. The incorporation of Caesalpinea spinosa (Tara) interspersed with S. saponaria allowed the contribution of its fruits to the productivity of the plot, since from its fruits we obtain tannins for tanning, natural dye, and gums for the food industry. Continuing with the practice of agroforestry, aromatic and medicinal species such as Aloe vera (Sábila), Chrysopogon zizanioides (Vetiver), and Cymbopogon citratus (Lemongrass) were placed between the two tree species. By means of Soxhlet extraction with ethanol, the soap and the dyes that were used as ingredients of the biological shampoo were obtained. Using a homemade steam distiller, the extraction of essential oils from the aromatic and medicinal species was achieved. The project began under Resolution N° 0448-2009-R-UNE, which authorized the reforestation of the Universidad Nacional de Educación Enrique Guzman y Valle (UNE) and surrounding areas with native plant species. The strategy used was that of the Biology and Ecology students acting as godmothers and godfathers of the trees considered in the project.